Incidence of hepatitis C among people who inject drugs in Ireland. Issue 1 (December 2016) - Carew, Anne; Murphy, Niamh; Long, Jean; Hunter, Kate; Lyons, Suzi; Walsh, Cathal; Thornton, Lelia
Abstract Background Comprehensive information on the incidence and duration of hepatitis C virus (HCV) infection for people who inject drugs (PWID) in Ireland is not available. We created an incidence curve of injecting drug use in Ireland and subsequently estimated incidence of hepatitis C virus (HCV) infection. Methods Anonymised data from the National Drug Treatment Reporting System (NDTRS) were used to identify all people who inject drugs (PWIDs) and who entered drug treatment for the first time between 1991 and 2014. A curve, estimating the incidence of injecting, was created to plot PWIDs by year of commencing injecting. The curve was adjusted for missing data on PWIDs in treatment and for PWIDs who were never treated. An adjustment was made to account for injectors who had never shared injecting equipment. The incidence of HCV infection and chronic infection in PWIDs was estimated by applying published rates. Results Between 1991 and 2014, 14, 320 injectors were registered on NDTRS. The majority were young (median age 25 years), male (74%), lived in Dublin (73%) and injected an opiate (e.g. heroin) (94%). The estimated total number of injectors up to the end of 2014 was 16, 382. An estimated 12, 423 (95% CI 10, 799-13, 161) were infected with HCV, and 9, 317 (95% CI 8, 022-9, 996) became chronically infected. The estimated annual number of new HCV infections among PWIDs increased steeply from the late 1970s and peaked in 1998. By 2014, almost 30% of injectors were estimated to have been infected for over 20 years. Conclusions This is the first comprehensive national estimate of the incidence of HCV in PWIDs in Ireland and will inform planning and developing appropriate health care services.